Improving Anti-listeria Activity of Thymol Emulsions by Adding Lauric Acid - Cai, Qizhen; Zhang, Yun; Fang, Xiaofeng; Lin, Suyun; He, Zhirong; Peng, Shengfeng; Liu, Wei (Frontiers in Nutrition, 2022)
In this study, a novel emulsion, Thymol (Thy) and lauric acid (LA) emulsion (Thy/LA-Emulsion) was prepared by homogenizing eutectic solvent (Thy/LA mixture) and caseinate solution. The effects of Thymol and lauric acid mass ratio on the formation, stability, and antibacterial activity of emulsions were studied. Compared with Thymol emulsion (Thy-Emulsion), the addition of lauric acid (25%, 50%, 75%) could enhance the antibacterial efficacy of the emulsions. Among then, Thy/LA25%-Emulsion could be stored at room temperature for a mouth without particle size increase, indicating that the stability of emulsions were unaffected by the addition of LA. Meanwhile, Thy/LA25%-Emulsion (3.06 ±0.12 cm) exhibited a greater inhibition zone, and required a lower concentration (0.125 mg/mL) to completely inhibit the growth of Listeria monocytogenes. Consequently, Thy/LA25%-Emulsion demonstrated the best antibacterial activity and physicochemical stability due to its long-term storage stability. Our results suggest that Thy/LA25%-Emulsions may become a more functional natural antibacterial agent with greater commercial potential owing to its cheaper raw materials, simpler production processes and better antibacterial effect in food industry.